2010
DOI: 10.1103/physrevc.82.025806
|View full text |Cite
|
Sign up to set email alerts
|

Half-lives and branchings forβ-delayed neutron emission for neutron-rich Co–Cu isotopes in ther-process

Abstract: The β-decays of very neutron rich nuclides in the Co-Zn region were studied experimentally at the National Superconducting Cyclotron Laboratory using the NSCL β-counting station in conjunction with the neutron detector NERO. We measured the branchings for β-delayed neutron emission (Pn values) for 74 Co (18±15%), and 75−77 Ni (10±2.8%, 14±3.6%, and 30±24%, respectively) for the first time, and remeasured the Pn values of 77−79 Cu, 79,81 Zn, and 82 Ga. For 77−79 Cu and for 81 Zn we obtain significantly larger P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
62
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 80 publications
8
62
0
Order By: Relevance
“…The speed of the r-process reaction sequence and the resulting abundances of the elements are significantly influenced by the β-decay properties of the nuclei involved, which are in turn directly related to the evolution of nuclear structure and deformation. In a recent measurement of the half life of the doubly-magic nucleus 78 Ni [8,9], it was shown that the persistence of the closed neutron and proton shells had a significant impact on the r-process abundance patterns, and theoretical predictions for the half life were significantly longer than observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The speed of the r-process reaction sequence and the resulting abundances of the elements are significantly influenced by the β-decay properties of the nuclei involved, which are in turn directly related to the evolution of nuclear structure and deformation. In a recent measurement of the half life of the doubly-magic nucleus 78 Ni [8,9], it was shown that the persistence of the closed neutron and proton shells had a significant impact on the r-process abundance patterns, and theoretical predictions for the half life were significantly longer than observed.…”
Section: Introductionmentioning
confidence: 99%
“…The results are used as a nuclear-structure probe to study the deformation of the β-decay mother/daughter system, which in turn can provide first hints of the underlying shell structure (see for instance Refs. [9,[16][17][18][19][20]). …”
Section: Introductionmentioning
confidence: 99%
“…Some studies show that neutron star mergers provide an important contribution to the solar system rprocess, but this is not enough to explain the abundances in the oldest observed stars, see e.g., [12][13][14]. In contrast, other models can explain the r-process abundances at all metallicities solely based on the neutron star merger scenario [15].Experimentally, there has been impressive progress in approaching r-process nuclei, see [16][17][18][19][20][21] and references quoted therein. New-generation radioactive ion beam facilities [22][23][24] will be able to reach a range of nuclei…”
mentioning
confidence: 99%
“…Experimentally, there has been impressive progress in approaching r-process nuclei, see [16][17][18][19][20][21] and references quoted therein. New-generation radioactive ion beam facilities [22][23][24] will be able to reach a range of nuclei never possible before, including the neutron-rich frontier of the nuclear landscape.…”
mentioning
confidence: 99%
“…A large effort has been devoted to the measurement of masses, β -decay half-lives, and β -delayed neutron emission probabilities (e.g. recently [3][4][5]), however, the majority of the r-process nuclei are still not accessible. In addition, although in many environments the neutron-capture reaction rates do not play significant role in the r-process flow due to (n, γ)-(γ, n) equilib- * spyrou@nscl.msu.edu † liddick@nscl.msu.edu ‡ a.c.larsen@fys.uio.no rium, recent studies have shown significant sensitivity to the neutron-capture reaction rates in certain conditions [6].…”
mentioning
confidence: 99%